Solid phase peptide synthesis of bombesin analogs bearing unnatural amino acids with fluorescente and metal chelating properties - Ribeiro, Gonçalo M. A. (2012)
In the present communication, we will report the solid phase synthesis and characterization of two bombesin analogues with unnatural amino-acids with both fluorescent and metal chelating properties.